2020
DOI: 10.1021/acs.jafc.0c02720
|View full text |Cite
|
Sign up to set email alerts
|

Novel Protein Tyrosine Phosphatase 1B Inhibitor-Geranylated Flavonoid from Mulberry Leaves Ameliorates Insulin Resistance

Abstract: Mulberry leaf is a common vegetable with a variety of beneficial effects, such as hypoglycemic activity. However, the underlying mechanism of its hypoglycemic effect have not been fully revealed. In this study, two flavonoid derivatives were isolated from mulberry leaves, a new geranylated flavonoid compound (1) and its structural analogue (2). The structures of compounds 1 and 2 were elucidated using spectroscopic analysis. To study the potential hypoglycemic properties of these compounds, their regulatory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 33 publications
0
16
1
Order By: Relevance
“…Interestingly, FA had no effect on PTP1B expression in hepatocytes, macrophages as well as HSCs, with or without the presence of different model drugs ( Supplementary Figures S5A–E ). Lines of evidence indicated that PTP1B dephosphorylated multiple protein kinases and caused the modulation of multiple signaling pathways ( Niu et al, 2020 ). Given that the regulatory effects of PTP1B on AMPK activation were not only affected by its expression but also relied on its phosphatase activity, FA might mediate AMPK phosphorylation through the regulation of PTP1B activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, FA had no effect on PTP1B expression in hepatocytes, macrophages as well as HSCs, with or without the presence of different model drugs ( Supplementary Figures S5A–E ). Lines of evidence indicated that PTP1B dephosphorylated multiple protein kinases and caused the modulation of multiple signaling pathways ( Niu et al, 2020 ). Given that the regulatory effects of PTP1B on AMPK activation were not only affected by its expression but also relied on its phosphatase activity, FA might mediate AMPK phosphorylation through the regulation of PTP1B activity.…”
Section: Resultsmentioning
confidence: 99%
“…There are several critical amino acid residues (Arg221, Ala217, Asp 48, Asp181, Gly183, Gly220, Lys116, Phe182 and Tyr46) of PTP1B were found to directly interact with potential inhibitors isolated from natural products (Jung et al, 2017;Sharma et al, 2020;Hu et al, 2021). Notably, Arg221 exerts an important function in optimizing salt bridge interactions with the phosphate bound to the catalytic site and stabilizing the phosphoryl-enzyme intermediator (Niu et al, 2020). Here we reported that Arg221 might play a vital role in the inhibition of PTP1B by FA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ROS-induced activation of the NF-кB pathway in skeletal muscle of HFD-fed mice has been associated with increased expression of PTP1B [ 55 ], a negative regulator of insulin signaling [ 56 ]. In this line, the transfection with PTP1B to HepG2 cells by Niu et al [ 57 ] decreased the transcription of IRS1 and GLUT4. Considering that several authors have previously reported inhibitory activities of OA and its derivatives on PTP1B [ 56 , 58 , 59 , 60 ], one of the possible mechanisms by which OA improves insulin sensitivity could be through inhibiting PTP1B.…”
Section: Discussionmentioning
confidence: 99%
“…In the ROESY spectra, correlations of H-13 with H-11 and H-2 supported the 11β-H and 13β-H in 10; correlations of H-11 with H 2 -14 and H-13 with H-2′/6′ indicated the 11β-H and 13α-H in 11; correlations of H-11/H-13 and H-13/H-2′(6′) verified the 11α-H and 13α-H in 12; correlations of H-11 with H 2 -14 and H-13 with H-2 suggested the 11α-H and 13β-H in 13. Thus, the structures of 10−13 were deduced and named as tsaokoflavanol J (10), tsaokoflavanol K (11), tsaokoflavanol L ( 12), and tsaokoflavanol M (13), respectively.…”
Section: T H Imentioning
confidence: 99%
“…According to the mode of action, the currently used oral hypoglycemic drugs are mainly classified as biguanides, α-glucosidase inhibitors, insulin secretagogues, insulin sensitizers, glucagon-like peptide-1 (GLP-1) receptor agonists, dipeptidyl peptidase-4 (DPP-4) inhibitors, and sodium-glucose cotransporter-2 (SGLT-2) inhibitors. , Among them, α-glucosidase inhibitors, for example, acarbose, miglitol, and voglibose, are considered promising antidiabetic drugs that can be used alone or in combination with other types of drugs, whereas the undesirable gastrointestinal side effects and weight gain are inevitable . It is well accepted that protein tyrosine phosphatase 1B (PTP1B) plays a key role in negatively regulating insulin action by dephosphorylation of activated insulin receptors and downstream substrate proteins, and thus, PTP1B inhibitors are fascinating candidates for developing antidiabetic agents. However, the clinical use of PTP1B inhibitors is severely impeded by their poor membrane permeability and weak selectivity against T-cell protein tyrosine phosphatase (TCPTP), the most similar protein to PTP1B . Therefore, compounds with α-glucosidase and/or PTP1B inhibitory effects will provide valuable clues in searching for new antidiabetic candidates.…”
Section: Introductionmentioning
confidence: 99%